Conservation of Major L1 and Variability of Minor L2 Capsid Late Protein Genes in Human Papillomavirus of Indonesia Variants - Nuswantara, Sukma; Prana, Titik K; Wulandari, Dwi; Widyowati, Henni; Anzela, Vera; Levy, Dea; Cahyadi, Petrus; Tjandra, Lukas D (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Human Papilloma VirusÂ (HPV) has an out standing feature for its vast intraspecies variability. Of all known 100 types orÂ more, 15 t ypes of them are classified as high riskÂ because of their occurrenceÂ inÂ more than 95% of cervical cancer cases. Among all genes in their genome, E6 and E7 genes are considered oncogenes and have close relevance with their pathogenicity, whilst L1 and L2 ge nes produce capsid proteins that directly interact with theirÂ hostÂ receptors.Â ConsideringÂ theÂ importanceÂ ofÂ L1Â andÂ L2Â inÂ host-receptorÂ relationship,Â weÂ triedÂ to investigate their molecular variability thereby uncover their specificity as Indonesian variant s. Here we reported about the conservation of L1 minor capsid protein and variability of L2 capsid protein among high-risk types Human Papilloma Virus (HPV). The results indicated that L1 DNA was relatively more conserved than its L2 counterpart Also it was indicated that the middle part of either L1 or L2 CDSâ showed more DNA variability than thoseÂ atÂ theirÂ upstreamÂ sequences.Â ItÂ isÂ concludedÂ thatÂ L2Â middleÂ sequencesÂ areÂ importantÂ factorsÂ for intraspecific variations found in HPV of Indonesian variants. Â Keywords: Human Papilloma Virus (HPV), L1 gene, L2 gene, cervical cancer, high risk HPV